Effects of The Linguistic Environment on Improving Speech Skill for Female Students of Dar Al-Rahman Institute for Islamic Education - Aslamiah, Nur; Susiawati, Wati; Raswan, Raswan; Muttaqin, Zainal (Al-Muyassar: Journal of Arabic Education, 2024)
The research aims to prove the role of the linguistic environment in improving the speaking skill of Arabic language learners in official institutions. As well as analyzing how to create a "linguistic environment" strategy that increases Arabic language proficiency. Thus, the researcher is able to reform the existing Arab environment and employ it in order to acquire Arab skills and promote academic production. As for the pure method that the researcher used, it is a quantitative method. The researcher used in collecting data is the observation, the interview and the distribution of questionnaires. The conclusion of this research is that the environment has an impact on the Arabic language skills of the students of Dar Al-Rahman Institute, from the results of the calculations between the variable X (linguistic environment) and the variable Y (speech skills). It was analyzed with the help of SPSS version 22. The number is shown as 0.524, which ranges from 0.40 to 0.70, which is based on the interpretation of the ‘r’ value for a moderate moment, which is based on the interpretation of the figures on the strength of the relationship between these two variables showing that between variables X and Y are included in the ‘average correlation’.